2018
DOI: 10.1371/journal.pone.0191893
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomically-linked growth phenotypes during arsenic stress among arsenic resistant bacteria isolated from soils overlying the Centralia coal seam fire

Abstract: Arsenic (As), a toxic element, has impacted life since early Earth. Thus, microorganisms have evolved many As resistance and tolerance mechanisms to improve their survival outcomes given As exposure. We isolated As resistant bacteria from Centralia, PA, the site of an underground coal seam fire that has been burning since 1962. From a 57.4°C soil collected from a vent above the fire, we isolated 25 unique aerobic As resistant bacterial strains spanning seven genera. We examined their diversity, resistance gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Finally, it is worth noticing that both arsenate reductase (codified by arrA or arsC genes) only amplified in cultures supplemented with As(III), and that the amplifications of two forms of the primers that codified for the arsenite oxidase was observed in the anaerobic culture supplemented with arsenate Ana(As 5+ 50 mM). Our results, together with other related studies, prove the need to increase the knowledge of microbial resistance mechanisms to improve the design of primers, not only for the characterization of species but, more importantly, to enable the use of specific resistance genes as markers of As environmental contamination .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Finally, it is worth noticing that both arsenate reductase (codified by arrA or arsC genes) only amplified in cultures supplemented with As(III), and that the amplifications of two forms of the primers that codified for the arsenite oxidase was observed in the anaerobic culture supplemented with arsenate Ana(As 5+ 50 mM). Our results, together with other related studies, prove the need to increase the knowledge of microbial resistance mechanisms to improve the design of primers, not only for the characterization of species but, more importantly, to enable the use of specific resistance genes as markers of As environmental contamination .…”
Section: Discussionsupporting
confidence: 66%
“…Even though our results are only preliminary, they show that in presence of As the tolerant consortia maintain acceptable µ values and reach approximately the same cellular concentrations than As‐free cultures, both desirable characteristic for the design of a bioremediation process. On this subject, it has been reported that microorganisms which develop faster might be better suited to cope with As contamination than those that present high Minimum Inhibitory Concentration (MIC) values .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this complexity, my lab advances multiple research directions. Our toolbox includes high-throughput omics (mainly sequencing and metabolomics), in situ field surveys and experiments, synthetic microbial communities ( 1 ), and quantitative methods in environmental microbiology and microbial isolation and characterization (e.g., reference 2 ). In addition, we ground our microbiome work in ecological theory and seek to identify and understand the ecological principles that explain overarching patterns across communities and ecosystems (e.g., references 3 and 4 ).…”
Section: Perspectivementioning
confidence: 99%
“…Our immediate future directions are to determine the composition and structure of the dormant soil microbiome, to understand their resuscitation dynamics given fire, and to quantify the contributions of rare and dormant members to functions. So far, we have evidence that members of the rare biosphere contribute to arsenic resistance ( 2 ) and therefore can have consequences for arsenic transformation in Centralia. We also found that the diverse taxa inhabiting fire-affected soils, on average, have smaller genomes, fewer two-component regulatory systems, and fewer antibiotic resistance and production genes ( 11 ; J. W. Sorensen, T. K. Dunivin, T. C. Tobin, and A.…”
Section: Perspectivementioning
confidence: 99%